Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1098/rsta.2021.0158
|View full text |Cite
|
Sign up to set email alerts
|

Opinion polarization in social networks

Abstract: In this paper, we propose a Boltzmann-type kinetic description of opinion formation on social networks, which takes into account a general connectivity distribution of the individuals. We consider opinion exchange processes inspired by the Sznajd model and related simplifications but we do not assume that individuals interact on a regular lattice. Instead, we describe the structure of the social network statistically, assuming that the number of contacts of a given individual determines the probability that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Focusing on changing the beliefs of key members, such as INFLs, of a polarized group may trigger a snowball effect in the beliefs of all members of the given community. The results in [123] suggest that this may be the case as they showed that most individuals from a network over time switch to opposite sentiments about the preconceived belief. The results obtained in [111] suggest that another possible way to revert polarization is to shield the members from their corresponding echo chambers, allowing them to access the ideas of members outside these chambers freely.…”
Section: Polarization Dimension As Shown In Tablementioning
confidence: 95%
“…Focusing on changing the beliefs of key members, such as INFLs, of a polarized group may trigger a snowball effect in the beliefs of all members of the given community. The results in [123] suggest that this may be the case as they showed that most individuals from a network over time switch to opposite sentiments about the preconceived belief. The results obtained in [111] suggest that another possible way to revert polarization is to shield the members from their corresponding echo chambers, allowing them to access the ideas of members outside these chambers freely.…”
Section: Polarization Dimension As Shown In Tablementioning
confidence: 95%
“…Even though, in general, the collision kernel can be given as a unique function of (x, x * , c, c * ), here we assume that it can be factorized in such a way that B(x, x * ) describes the influence of the neuron location on the interactions, while G(c, c * ) refers to their degree of connections. Substituting (11) into (12) we get…”
Section: Spatially Inhomogeneous Casementioning
confidence: 99%
“…This means that, unlike gas molecules, the interactions among the considered particles are mediated by a background graph structure discriminating which interactions may actually take place and at which rate. Examples of kinetic descriptions of networked interactions can be found, for instance, in opinion formation problems [7,12,19] or in the modeling of the spread of infectious diseases [13]. In these problems, the background network may enter the big picture in essentially two ways.…”
Section: Introductionmentioning
confidence: 99%
“…Loy et al [ 25 ] propose a Boltzmann-type kinetic description of opinion formation on social networks, which takes into account a general connectivity distribution of the individuals. The opinion exchange processes considered here were inspired by the Sznajd model and related simplifications but the individuals are not placed on a regular lattice, nor it is the case of mean field interaction as was the case for few of the above-mentioned studies.…”
Section: Kinetic Exchange Models Of Opinion Formationmentioning
confidence: 99%